Tata Kelola Kapal dan Kinerja Keselamatan Pelayaran - Beny Jackson Maliota; David A. Lasse; Aswanti Setyawati (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2020)
The research objective was to determine the effect of marine inspector capabilities on ship governance and shipping safety performance at PT Vallianz Offshore Maritime, 2019. The study used the survey method. The sample is 59 skippers taken by census technique. Data analysis used descriptive statistics and inferential statistics on path analysis. The results showed: marine inspector's capability has a positive and very significant direct effect on shipping safety performance, ship governance has a positive and very significant direct effect on shipping safety performance, the capability of marine inspector has a positive and very significant direct effect on ship governance, and marine inspector capability positive and very significant indirect effect on shipping safety performance by mediating ship governance. The conclusion of the study is marine inspector's capability to influence shipping safety performance by mediating ship governance,so that shipping safety performance can be improved through marine inspector's capability and ship governance.